2014
DOI: 10.1097/qai.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Effect of Zinc Supplementation in HIV-Infected Children Receiving Highly Active Antiretroviral Therapy

Abstract: Supplementation of 20 mg zinc daily for 24 weeks did not have any statistically significant effect on the increase in CD4%, decrease in viral load, anthropometric indices, and morbidity profile in HIV-infected children started on ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A literature review found numerous studies that reported an inconclusive effect of zinc on CD4 ? T-lymphocyte recovery in PLWHA [14][15][16][17][18][19][20][21][22]. However, we also found multiple studies that promoted the benefit of zinc in PLWHA [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A literature review found numerous studies that reported an inconclusive effect of zinc on CD4 ? T-lymphocyte recovery in PLWHA [14][15][16][17][18][19][20][21][22]. However, we also found multiple studies that promoted the benefit of zinc in PLWHA [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 95%
“…Zinc has been studied as a treatment modality for antiretroviral-induced diarrhea, appetite stimulation and an adjunct in viral suppression. A literature review found numerous studies that reported an inconclusive effect of zinc on CD4 + T-lymphocyte recovery in PLWHA [ 14 – 22 ]. However, we also found multiple studies that promoted the benefit of zinc in PLWHA [ 23 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin concentrations increased between baseline and 6 weeks postpartum in both groups, but the increase in hemoglobin as well as packed cell volume and red blood cell count were significantly lower in the zinc group compared with the placebo arm. In a recent RCT, the investigators randomized 52 children older than 6 months starting HAART to receive daily 20 mg zinc supplementation or placebo for 24 weeks [92]. There was no difference between the two arms in CD4 + percentage increase, viral load reduction, anthropometric indices, and morbidity.…”
Section: Zincmentioning
confidence: 94%
“…Bobat et al reported no effect of zinc supplementation on CD4+ counts among 96 HIV-infected children in South Africa [52]. Although the median CD4% value of the zinc group rose from 10% to 23% at 12 weeks and to 24.5% at 24 weeks, higher than the placebo group which changed from 11% to 20% at 12 weeks and to 22% at 24 weeks, the trend toward a higher increase in the zinc group is not statistically significant [48]. They calculated no difference in the mean percentage of CD4+ between the zinc and placebo groups (Irlam et al, [53]).…”
Section: Effects Of Intervention (Zinc) On Cd4+ Countsmentioning
confidence: 95%